Research Map of English Study Program Lecturers STAIN Mandailing Natal: Systematic Literature Review - Hasyimsyah Batubara, Muhammad; Dara Ilfa Rahila, Cut; Ayu, Fitri (Jumper: Journal of Educational Multidisciplinary Research, 2025)
This study aims to map the direction, trends, and scientific contributions of the publications of lecturers of the English Tadris Study Program of STAIN Mandailing Natal in the 2020-2025 time span using the Systematic Literature Review (SLR) approach. A total of 94 articles written by active lecturers that met the inclusion criteria were reviewed thematically and methodologically. The analysis showed that the most dominant topics were English language teaching (EFL/ELT), the use of media and technology in learning, and the development of contextual teaching materials based on local and Islamic values. The research also highlighted contributions in sociolinguistics, pragmatics, psycholinguistics, and community service. The most widely used research methods are experiments and descriptive qualitative studies. In addition, there is a positive trend in the use of SLR and bibliometrics, which reflects the increasing methodological literacy of lecturers. These findings reflect the dynamics of research that is adaptive to technological developments, oriented towards pedagogical innovation, and rooted in local values. This study makes a strategic contribution to the development of a research roadmap and the improvement of academic quality in Islamic higher education.